Structure research of nanoscaled silicon carbide detonation coatings of tribotechnical application - Dovhal, A.H.; Pryimak, L.B. (Problems of Tribology, 2022)
Presented studies are related to the spheres of wearproof coating development. World wear resistance improvement technology experience has accumulated a huge amount of statistical material on the failure due to increased level of parts wear. That is why the issue of research and improvement of anti-wear properties of machine elements is one the components when considering the priority directions of ensuring the reliability of operation motor vehicles and friction units. The SiC coating has been deposited on the medium carbon steel using detonation deposition. It has been established that it is very sensible for modes of coating deposition and different physical and chemical phenomenon have been detected. The structure of the obtained coating has been thoroughly researched on the electronic microscope. The obtained coating has been developed for testing on the friction bench modeling the friction process that is taking place in the couple of main and rod journals of internal combustion engines. The coating has also the corrosion protection. The new magnet modified method of detonation coating deposition has been tested for deposition of nanoscaled coating on mild carbon steel. The optimal modes of the magnet modified coating deposition for silicon carbide powders batch mixture from the viewpoint of structure formation have been detected.